2005
DOI: 10.1074/jbc.m410731200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Enhancer That Controls Up-regulation of Fibronectin during Differentiation of Embryonic Stem Cells into Extraembryonic Endoderm

Abstract: The extraembryonic endoderm is derived from inner cell mass cells of the blastocyst during early mouse embryogenesis. Formation of the extraembryonic endoderm, which later contributes to the yolk sac, appears to be a prerequisite for subsequent differentiation of the inner cell mass. While embryonic stem cells can be induced to differentiate into extraembryonic endoderm cells in vitro, the molecular mechanisms underlying this process are poorly understood. We used a promoter trap approach to search for genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…This Sox17 heterozygous mutant on a B6 background therefore provides a clinically relevant experimental model for congenital biliary atresia and embryonic hepatitis elicited secondarily by malformations of extrahepatic bile duct. It is well known that SOXF factors (including SOX17) are involved in the expression of the fibronectin 1 (Fn1) (Shirai et al, 2005) and laminin, alpha 1 (Lama1) (Niimi et al, 2004) genes encoding constituents of the basement membrane. Moreover, previous studies have demonstrated that SOX17 functions as a transcriptional regulator in the basal lamina formation of the extra-embryonic endoderm (Shimoda et al, 2007) and parietal endoderm (Artus et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This Sox17 heterozygous mutant on a B6 background therefore provides a clinically relevant experimental model for congenital biliary atresia and embryonic hepatitis elicited secondarily by malformations of extrahepatic bile duct. It is well known that SOXF factors (including SOX17) are involved in the expression of the fibronectin 1 (Fn1) (Shirai et al, 2005) and laminin, alpha 1 (Lama1) (Niimi et al, 2004) genes encoding constituents of the basement membrane. Moreover, previous studies have demonstrated that SOX17 functions as a transcriptional regulator in the basal lamina formation of the extra-embryonic endoderm (Shimoda et al, 2007) and parietal endoderm (Artus et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Intronic cis-elements, such as enhancers or repressors, have been reported for various genes [31][32][33][34][35][36]. However, only a few studies have reported polymorphisms in the intron region of genes that determine susceptibility to complex disease traits that might function as an enhancer or repressor regulating the expression level of the gene in pathology, including rs243480 in intron 3 of the Cullin1 (CUL1) gene significantly associated with rheumatoid arthritis [37], rs909253 in intron 1 of the LTA gene and rs7291467 in intron 1 of the LGALS2 gene associated with myocardial infarction [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a role for FN in determining cell phenotype, increased FN expression is associated with differentiation of embryonic stem cells (Shirai et al, 2005). Increased FN deposition contributes to a number of pathological conditions, including hepatic (Kershenobich Stalnikowitz and Weissbrod, 2003) and pulmonary fibrosis (Crouch, 1990;Hetzel et al, 2005), and diabetic nephropathy, retinopathy, and macroangiopathy (Andresen et al, 1996;Hohenadel and van der Woude, 2004).…”
Section: Introductionmentioning
confidence: 94%